2007
DOI: 10.1007/s11199-007-9324-z
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Managerial Discourses in Sport Organizations: Multiplicity and Complexity

Abstract: The lack of women in senior management functions in sport may in part be attributed to dominant discursive managerial practices in sport organizations. The purpose of this study is to explore ways in which the discourses and their subtexts used by directors of Dutch national sport organizations to talk about their work, sustain homologous reproduction. Close reading of the transcripts of interviews by both researchers followed by a continuous cycle of data reduction and verification and researcher agreement en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…Sport organizations often promote traditional gender roles, and male privilege and dominance (Claringbould & Knoppers, 2007;Knoppers & Anthonissen 2008). Therefore, it is not surprising that women are still under-represented in leadership positions and marginalized in the sport workplace (Acosta & Carpenter, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sport organizations often promote traditional gender roles, and male privilege and dominance (Claringbould & Knoppers, 2007;Knoppers & Anthonissen 2008). Therefore, it is not surprising that women are still under-represented in leadership positions and marginalized in the sport workplace (Acosta & Carpenter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of men to occupy influential positions in sport organizations is natural and mostly unquestioningly accepted (e.g., Knoppers and Anthonissen 2008;Pfister 2006). Several researchers observed that senior management roles are heavily dominated by masculine discourse (e.g., Shaw and Frisby 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sports organizations at the national level are only partially funded by the state and more often through lottery funding. In previous work based on the larger project, we explored connections between constructions of managerial work and masculinities (Knoppers and Anthonissen 2005), the gendering of discourses about managerial work in sports organizations (Knoppers and Anthonissen 2008), and how managers in nonprofit organizations construct a relationship between their history of involvement with sport and managerial skills (Knoppers 2011). We attempted to collect data from a heterogeneous population.…”
Section: Methodsmentioning
confidence: 99%
“…This discourse can be congruent with an approach to human resource management in which managers see them as acting in the best interests of the organisation by adopting communication skills (Kerfoot & Knights, 1998;Knoppers & Anthonissen, 2008). Wacjman (1998), who studied male and female managers in five multinational companies, found that the emphasis on interaction abilities has meant that male managers have added these skills to their repertoire so that women are not really needed to contribute these skills to organisations.…”
Section: Correspondence Analysismentioning
confidence: 99%
“…This passion must not be disordered, however, but be controlled. This emphasis on control would allow the use of this discursive practice to be associated with masculinities instead of femininities (Knoppers & Anthonissen, 2008).…”
Section: Correspondence Analysismentioning
confidence: 99%